Non‐Invasive Diagnostics: Integrated Devices for Non‐Invasive Diagnostics (Adv. Funct. Mater. 15/2021). (8th April 2021) - Ates, Hatice Ceren; Brunauer, Anna; von Stetten, Felix; Urban, Gerald A.; Güder, Firat; Merkoçi, Arben; Früh, Susanna Maria; Dincer, Can
Abstract : In article number 2010388, Can Dincer and co‐workers present integrated "sample‐to‐answer" diagnostic platforms including wearable, handheld, and tabletop devices for non‐invasive monitoring. Factors influencing the translation of these devices from the fundamental research phase through the commercialization and into our daily life are discussed via the technology readiness level concept. Image designed by Ceren Ates and created by Ella Maru Studio.